USING R FOR ANALYZING FINANCIAL MARKETS - Nicolae-Marius JULA; Nicoleta JULA (Challenges of the Knowledge Society)
Financial markets are hard to analyse and almost impossible to predict. The progress in computer technology means also the improvement of the available tools for the analysts to observe the evolution of financial markets. The R software, besides different statistical analysis, offers also the tools to process and analyse the data from these markets, in a free and accessible manner.